2020
DOI: 10.1111/ene.14177
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and longitudinal associations between probable rapid eye movement sleep behavior disorder and impulse control disorders in Parkinson’s disease

Abstract: Background and purpose: The aim was to investigate whether probable rapid eye movement sleep behavior disorder (pRBD) is associated with impulse control disorders (ICDs) in drug-na€ ıve patients with Parkinson's disease (PD) and whether baseline pRBD is associated with a higher incidence of ICDs during follow-up. Methods: The Parkinson's Progression Markers Initiative is an international, multicenter, prospective cohort study to identify biomarkers of PD progression. In all, 423 drug-na€ ıve patients with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recently, a meta‐analysis including 10 observational cross‐sectional studies and involving data from 2,781 PD patients found that RBD was associated with a >2‐fold increased risk of developing ICBs, even after stratifying subgroups based on methods for diagnosing RBD and ICBs 18 . Finally, another longitudinal analysis was recently performed using the PPMI cohort data, finding that pRBD at BL was an independent predictor of ICD development over time 19 . However, a cutoff of ≥5 on the RBDSQ was used to define pRBD, as in the general population, whereas a cutoff of ≥6 has been shown to be the best value for detecting RBD in PD 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a meta‐analysis including 10 observational cross‐sectional studies and involving data from 2,781 PD patients found that RBD was associated with a >2‐fold increased risk of developing ICBs, even after stratifying subgroups based on methods for diagnosing RBD and ICBs 18 . Finally, another longitudinal analysis was recently performed using the PPMI cohort data, finding that pRBD at BL was an independent predictor of ICD development over time 19 . However, a cutoff of ≥5 on the RBDSQ was used to define pRBD, as in the general population, whereas a cutoff of ≥6 has been shown to be the best value for detecting RBD in PD 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although one study assessed longitudinal severity of ICBs and its predictors in PD using multiple imputation analysis, 17 to date only one longitudinal study has assessed whether RBD is a possible risk factor for the development of incident ICBs 19 . This study, using Parkinson's Progression Markers Initiative (PPMI) cohort data, found that pRBD at baseline (BL), defined by a score ≥ 5 on the RBD Screening Questionnaire (RBDSQ), was an independent predictor of ICD development over time, after adjusting for some covariates (sex, age of disease onset, disease severity and duration, cognitive abilities, anxiety, and depression).…”
Section: Introductionmentioning
confidence: 99%
“…PD patients with ICDs show a higher level of neuroticism and lower levels of agreeableness and conscientiousness [58], particularly among PD patients with pathological gambling [66] or hypersexuality [10]. Such patients are also reported to have ineffective coping skills [67], premorbid personality (novelty seeking and harm avoidance) [60], and anxiety [68].…”
Section: Personality Traitsmentioning
confidence: 99%
“…They may show different neuropsychological profiles depending on ICD subtype, with distinct dysexecutive or memory impairments [13,76]. But these alterations may be reversible [68,82,[84][85][86][87][88], although some recent findings did not reproduce this association [88,89].…”
Section: Cognitionmentioning
confidence: 99%
See 1 more Smart Citation